1481 Trends in Paediatric Acute Asthma Management in the Republic of Ireland: A Comparison Between Community and Hospital Practice. (October 2012) - Cronin, J; Pollock, J; Grant, T; McCoy, S; Breen, N; Walsh, S; O'Sullivan, R
Abstract : Introduction: The prevalence of childhood asthma in Ireland is amongst the highest in the world. We aim to compare the management of this condition by Emergency Physicians (EPs), Paediatricians and community-based General Practitioners (GPs). Methods: A standardised online anonymous survey was conducted of senior EPs, Paediatricians and General Practitioners (GPs) in Ireland. 15% of GPs nationally were chosen using a computerised randomization method. A postal survey was sent to those GPs for whom an email address was not available. Results: We received 344 responses, giving an overall response rate of 52.3% (EP: 67.6%; Paediatricians: 51.3%; GP: 50.6%). Over 70% of paediatricians and EPs use spacer devices for mild and moderate episodes; 78% of GPs use spacers for mild asthma, however this drops to 38% for moderate episodes. Paediatricians and EPs differed in their choice of first-line intravenous bronchodilators with paediatricians choosing salbutamol (48.3%) most frequently and EPs choosing magnesium (48.3%). Whereas almost all respondents felt that severe asthma should be referred to an ED, over 85% of paediatricians and EPs felt that moderate attacks should be referred compared to 13.7% of GPs. Over 90% of all respondents would welcome a national guideline on the management of acute paediatric asthma exacerbations. Conclusion: This is the first study of its kind internationally to compare management of this important and common condition across the relevant specialties. The results of this survey support the development of a national guideline for acute paediatric asthma management.